RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KESEHATAN KLINIK PRATAMA UNIKAL HEALTH CENTER (UHC) - Danang Satrio; Ristiawati Ristiawati; Nur Susanti (LPPM Universitas Pekalongan, 2022)
The success of health management is largely determined by the availability of health data and information. This data and information serve as the basis for decision-making in the health sector. To obtain quality health data and information, and accurate health information system is needed. The development of a strong Health Information System in producing quality information in decision-making in the health sector requires knowledge of the basic concepts of the health information system itself and the basics in its development. Primary Clinic Unikal Health Center (UHC) is a public clinic under the auspices of a private university called Pekalongan University. The problem that is still encountered is that the recording of medical record data is still not optimal because it is done manually so it is still less effective and efficient in processing the data. Based on this, it is necessary to develop a health management information system to be implemented at the Unikal Health Center (UHC) Primary Clinic. The purpose of this study is to replace the manual recording and data processing system with computerization, to overcome the obstacles that often occur related to the inability to provide information quickly, accurately, and on time with the management information system of the Unikal Health Center Clinic. (UHC) the required reports can be available instantly, such as patient reports, doctor reports, registration reports, medical record reports, prescription reports, and other data. The final result of this research is a prototype of the health information management system of the UHC Pratama clinic.